Analysis of Environmental Literacy and Sustainable Development Goals (SDGs) Competence among Community Leaders: Bases for Technology-Assisted Module for Green Management Advocates - Jimlan, Juim; Arias, Evan Anthony (Journal of Interdisciplinary Perspectives, 2025)
Environmental sustainability is a growing concern globally, and in the Province of Aklan, the need for strong community leadership in addressing ecological challenges has become increasingly urgent. This study aimed to assess the environmental literacy and Sustainable Development Goals (SDG) competence of community leaders in Aklan and to evaluate the effectiveness of a technology-assisted green management module in enhancing these competencies. Utilizing an explanatory-sequential mixed methods design, the study first collected quantitative data from 210 community leaders through validated questionnaires and qualitative insights from focus group discussions and in-depth interviews. Colaizzi’s phenomenological method and the Knowledge, Attitudes, and Practices (KAP) framework were used for thematic analysis. Key findings revealed a high level of environmental literacy and SDG competence across most demographic groups, with the LGBTQ+ and older participants scoring highest. A strong positive correlation (r = 0.952, p< 0.001) was found between environmental literacy and SDG competence. However, younger leaders exhibited lower engagement, and systemic barriers such as a lack of mentorship, decision-making power, and policy enforcement hindered broader participation in sustainability efforts. The green management module, delivered via Facebook, significantly improved participants’ knowledge, attitudes, and behaviors, as evidenced by pre- and post-assessment results. The study concludes that targeted, inclusive, and technology-driven training can strengthen sustainability leadership at the community level. It recommends expanding youth involvement, integrating traditional ecological knowledge, and fostering multi-stakeholder collaboration to achieve long-term environmental resilience in Aklan.